SIMCAQ: A Sociotechnical Diagnosis - Mathias, Eduardo; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
SIMCAQ, a Student Cost Quality Simulator, is a free online system to estimate the cost of providing quality education in public primary education schools. The purpose of SIMCAQ is to serve as an educational planning tool emphasizing the budgetary aspect, which diagnoses the educational context at municipal, state, and national levels. Allowing to simulate the annual budget required for up to 10 years, the system can contribute to changing the concept of financing primary education to guarantee the right to free, quality public education for all children, young people, and adults in Brazil. Since 2008, the system has gone through different stages of development. However, despite having clear objectives in its various project phases and an open code for consultation, the project suffers from problems that may affect its continuity and no study has investigated its situation. Due to the sociotechnical nature of the system, it is necessary to analyze whether it is achieving its objectives as a social contribution and evolving technically with each version developed. This research presents a sociotechnical diagnosis of the SIMCAQ project using Organizational Semiotics and qualitative analysis methods as a theoretical and methodological foundation. The results detail how the SIMCAQ project is evolving in conception, functionality, and design at each stage, and present (technical, methodological, organizational) problems of the project at the current stage that must be minimized if the project is to continue achieving its objectives as a social technology.